Application of Digital Technology in Marketing Plan: Case Study of the Company's Strategic Transformation - Wirawan*, Setia Teguh; Budianto, Irawan RD (Riwayat: Educational Journal of History and Humanities, 2024)
Digital transformation is a dominant phenomenon in the global economy today, mainly triggered by advances in digital technology. This article discusses the impact of digital transformation, particularly in the context of business models and corporate strategy. With a focus on the manufacturing sector, Society 5.0, and dramatic societal changes, this article presents statistical data related to the use of digital technology in Indonesia. Digital transformation encourages companies to adopt innovative technologies and new business models to gain a competitive advantage. An effective digital business strategy is crucial in facing the demands of contemporary society and achieving the Sustainable Development Goals. This research uses a literature study method to analyze the impact of digital transformation on business model innovation, focusing on successful and less successful cases. The research results highlight the importance of digital leadership, digital maturity, and innovation strategies in facing digital transformation challenges. This research provides a comprehensive picture of digital transformation, emphasizing the need for investment in digital technology and skills, as well as adapting to changes in the economy and society.